Comparison of Perceptions about Blood Donation among Medical Students and General Public - Zaheer, Najeebullah; Munir, Moizza; Fatima, Akhlas; Fatima, Eeshal; Tariq, Roman; Sultan, Faisal (Students’ Supplement of Journal of Rawalpindi Medical College, 2024)
Objectives: To compare the perceptions about blood donation among medical students and the general public and to analyze different motivating factors for blood donation. Materials and Methods: A comparative cross-sectional study was carried out from September 2022 to June 2023 among 1st and 2nd year medical students of Rawalpindi Medical University (RMU) and general public. 306 total participants with an equal number (n = 153) from each group were enrolled in the study by consecutive non-probability sampling. Data was gathered by a structured questionnaire. Participants’ score was ranked as poor (1-3), fair (4-6), and good (7-8) based on their perception. Data was analyzed by using SPSS version 27.0. Descriptive statistics were applied. Pearson chi-square test was applied to evaluate the connection between values. P-value <0.05 was considered significant. Results: 50.9% and 52.9% males were from medical college and general population respectively. Self-satisfaction was the main motivator among students (84.9%) and general community (71.2%). The main barrier to blood donation among 84.9% medical students was the perceived fear of blood screening while among general public it was the lack of dedicated outreach by organizations requesting blood donations. Conclusion: Medical students knew more about blood donation than general public. The main motivation for blood donation in both groups was self-satisfaction, while the main obstacle for medical peers was the need for blood screening & in the nonmedical group was a lack of outreach by an organization seeking blood donation.